Nanolayer research : methodology and technology for green chemistry - 今栄, 東洋子 (Elsevier, 2017)
This book introduces the advanced researches of nanolayers under noting recent trends of methodology and technology from basic to application for green science ) principle of nanolayers (2) methodology and technology of nanolayers (3) application of nanolayers